Programmability of Territorial Systems Organizability and Its Impact on Evolutionary Phenomena - Petlin, V. M. (Ukrainian Geographical Journal, 2025)
The study aims to reveal the phenomenon of programmability at all stages of the organizational development of natural territorial systems, where the concept of “programmability” is considered as directed management by the relevant territorial entities.  The consequence is the emergence of an internal functional structure in the territorial systems and the formation of their invariant properties.  Based on the totality of dependencies that control the phenomena of programmability, the existence of purposeful development in systems has been explained, which allows them to be within the limits of invariant variability and, thus, to influence the preservation of intersystemic functional quasi-equilibrium.  It has been shown that the stable organization of natural territorial systems is impossible without the phenomenon of programmability.  It is just this organization that ensures the emergence of functional integrity in them and ensures directed evolutionary changes.  From the origin to the qualitative development (destruction), systems go through several natural evolutionary stages, which do not arise randomly but due to the programmed maintenance of the systems (a kind of arrow of evolutionary variability) in the corridor of purposeful development.  As a result, intersystem relationships do not receive critical values since common intersystem programmability provides the corresponding part of the landscape sphere with stability against the background of multifaceted variability.  The development of the territorial systems’ organizability is always an integration phenomenon.  It is the integration that makes organizability a holistic effect.  As for the programs of evolutionary development of natural territorial systems, the phenomenon of integration here has an informational character.  Moreover, the integration of processes and relationships creates a programmable system in its entirety.  Such an entirety is the organized one that develops in a programmable way.  Therefore, programs for the evolutionary development of natural territorial systems as integrity are not a totality of the programmable components but a new programmable quality that is self-programmed but at the same time does not lose its general goal—to control the evolutionary development of territorial systems.
Keywords: programmability; programmable organizability of systems; programmability of evolutionary development of systems